Storybook validation: Essential practices for student's financial literacy - Okto Irianto; Susanto Susanto; Henie Poerwandar Asmaningrum; Adi Maulana Rachman; Jarot Budiasto; Habib Sokheh (Goodwood Publishing, 2024)
Purpose: To develop and validate a financial literacy storybook for Junior High School students using the 4D (Define, Design, Develop, Disseminate) method. Research Methodology: This study employs a development research approach, specifically utilizing the 4D (Define, Design, Develop, Disseminate) method to create and validate a financial literacy storybook for Junior High School students. Results: High feasibility scores from both material (72 points) and media (77 points) experts validated the storybook's content accuracy, relevance, and overall design quality. These results suggest that the approach of using digital storytelling, specifically through Storyjumper, can effectively bridge the gap between abstract financial concepts and relatable age-appropriate narratives for adolescents. Conclusions: The validated storybook enhances students’ financial literacy by combining pedagogical accuracy with engaging design, and digital storytelling innovatively boosts understanding and interest in financial education. Limitations: First, the validation process relied primarily on expert opinions, which, although valuable, may not fully capture the perspectives of the target audience, Junior High School students. The study did not include a pilot test with actual students, which could provide insights into the storybook's real-world effectiveness and engagement levels. Additionally, the research is limited to a specific geographical and cultural context, potentially affecting the generalizability of the findings to other regions or educational systems. Contribution: This research contributes a validated financial literacy storybook for Junior High School students, advancing educational tools in this crucial field and demonstrating the 4D method's effectiveness in educational material development.